2000
DOI: 10.1523/jneurosci.20-09-03085.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Group II Metabotropic Glutamate Receptors Inhibits Synaptic Excitation of the Substantia Nigra Pars Reticulata

Abstract: Loss of nigrostriatal dopaminergic neurons in Parkinson's disease (PD) leads to increased activity of glutamatergic neurons in the subthalamic nucleus (STN). Recent studies reveal that the resultant increase in STN-induced excitation of basal ganglia output nuclei is responsible for the disabling motor impairment characteristic of PD. On the basis of this, it is possible that any manipulation that reduces activity at excitatory STN synapses onto basal ganglia output nuclei could be useful in the treatment of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 51 publications
4
82
1
Order By: Relevance
“…All whole-cell patch-clamp recordings were obtained as described previously (Marino et al, 1998;Bradley et al, 2000). Fourteen-to 18-d-old Sprague Dawley rats were used in all experiments.…”
Section: Materials (Rs)-35-dihydroxyphenylglycine (Dhpg) L(ϩ)-2-ammentioning
confidence: 99%
“…All whole-cell patch-clamp recordings were obtained as described previously (Marino et al, 1998;Bradley et al, 2000). Fourteen-to 18-d-old Sprague Dawley rats were used in all experiments.…”
Section: Materials (Rs)-35-dihydroxyphenylglycine (Dhpg) L(ϩ)-2-ammentioning
confidence: 99%
“…In brain synapses such as the central nucleus of the amygdala (Neugebauer et al, 2000), hippocampal perforant path (Kilbride et al, 1998(Kilbride et al, , 2001, medial prefrontal cortex (mPFC) (Marek et al, 2000), nucleus accumbens (Robbe et al, 2002), and substantia nigra (Bradley et al, 2000), LY354740 has been shown to suppress evoked glutamate excitatory synaptic potentials/ currents (reviewed by Schoepp et al, 2003). In particular, the intra-amygdalar injection of LY354740 disrupted fearpotentiated startle (Walker et al, 2002), and intrahippocampal injection of LY354740 produced an anticonflict effect in the Vogel drinking test (Tatarczynska et al, 2001), suggesting that these regions may be involved in the anxiolytic actions of LY354740 when it is administered systemically.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this indicates a true species difference between rodents and primates regarding the presynaptic localization of mGluR2 in the pallidal complex or relies upon technical differences in the sensitivity of the different antibodies used in these studies remains to be established. It is worth noting that functional group II mGluRs were found to be expressed on putative STN glutamatergic terminals in the rat SNr (Bradley et al, 2000). If the intense mGluR2 immunolabeling seen in the human pallidum corresponds to presynaptic STN terminals, the group II mGluRs become a very promising target to reduce the release of glutamate from hyperactive subthalamopallidal terminals in PD.…”
Section: Metahotropk Glutamate Receptor^mentioning
confidence: 99%
“…Another mGluR subtype of interest for PD therapy is mGluR2, which was found to be expressed on subthalamonigral terminals in rats (Bradley et al, 2000). Furthermore, activation of these receptors in brain slices reduces glutamatergic transmission at subthalamonigral synapses (Bradley et al, 2000) and systemic administration of group II agonist reverses haloperidolinduced catalepsy (Bradley et al, 2000).…”
Section: Metabotropic Glutamate and Gaba-b Receptors: Novel Therapeutmentioning
confidence: 99%